Development of multimedia training material for RV-500 - Marcelo, Nancy R. (Animo Repository, 2006)
This report deals with the activity undergone by the trainee during the period of the practicum program as well as the special project accomplished by the trainee as a requirement of the program. The Bulacan State University serves as the industry partner of the trainee. The special project accomplished by the trainee is the development of multimedia training material for RV 500. The report is subdivided into four chapters. Chapter 1 discusses the company profile of Bulacan State University as well as the objectives of the practicum program and the significance of the practicum project. Chapter 2 includes the activity undergone by the trainee during the whole period of the practicum program. The practicum schedule starts on November 7, 2005 and ends on June 24 2006. The activities performed by the trainee includes orientation on the different equipment inside the Automation Center of the College of Engineering training on the functions and basic operations of RV 500, development of multimedia training material for RV 500 and documenting the necessary information for future use. This chapter also includes the problems encountered in the whole course of the practicum program as well as the solutions to the problems and lessons learned. The development of multimedia training material for RV 500 is presented on Chapter 3. This chapter discusses the practicum project accomplished by the trainee. It also includes the objective of the practicum project as well as the statement of the problems. Screen shot of the training material for RV 500 is also provided in this chapter. Evaluations conducted by the expert in terms of content, usability readability and instructional design are also included in this chapter. The last chapter includes the summary and conclusions of the practicum program as well as the practicum project.